1993
DOI: 10.1139/v93-251
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic study of the carbocation route from tetrahydrodicyclopentadiene to the adamantane ring

Abstract: . Can. J. Chem. 71, 2016Chem. 71, (1993. The energy profile for the transformation of the endo-tetrahydrodicyclopentadienyl cation A into the 1-adamantyl cation R has been probed by means of six separate experiments employing superacid techniques. Of the approximately 14 cations between A and R , required as intermediates for the above transformation, it can be shown that only one of these is capable of direct observation. This cation, the tricyclo[5.2.1.03~8]dec-3-yl (homobrendyl) cation J , is characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…We would like to re-open a discussion of the camphenyl chloride 2 −isobornyl chloride 3 rearrangement because of two recent developments: (1) Theoretical calculations , have shown that the secondary isobornyl cation in Meerwein's proposal does not exist as a stationary point on the camphenyl−isobornyl cation potential energy (PE) surface. (2) Any camphenyl chloride 2 → isobornyl chloride 3 mechanism must account for both a C−C bond shift and a chlorine atom shift.…”
mentioning
confidence: 99%
“…We would like to re-open a discussion of the camphenyl chloride 2 −isobornyl chloride 3 rearrangement because of two recent developments: (1) Theoretical calculations , have shown that the secondary isobornyl cation in Meerwein's proposal does not exist as a stationary point on the camphenyl−isobornyl cation potential energy (PE) surface. (2) Any camphenyl chloride 2 → isobornyl chloride 3 mechanism must account for both a C−C bond shift and a chlorine atom shift.…”
mentioning
confidence: 99%
“…Lajunen and Hirvonen [8] proposed an unspecified carbocation intermediate in norbornadiene hydration. Detection of bridged carbocations in water may not be possible with current techniques, as indicated by the need for nonpolar solvents and low temperature (−78°C) required to detect adamantane carbocations [10]. Hydration of the carbocations appears rate limiting since the observed similarity of hydration rates of quadricyclane and norbornadiene indicates that protonation and carbocation formation is rapid relative to hydration.…”
Section: Resultsmentioning
confidence: 99%
“…The molecules studied in this work are the isomers of C 10 H 16 (isomer set) and carbocationic rearrangements involving C 10 H 15 + (reaction set), shown in Tables 1 and 2. The isomers and chemical reactions selected for quantum chemical modeling were inspired by the earlier works of Engler et al 74 and Kirchen et al 75 These two earlier works highlight the efforts in the 1970s on adamantane isomers and substituted adamantanes through both experimental thermochemistry and computational molecular mechanics, which led to great improvements in both techniques. 76,77 In the work of Engler et al , the relative stabilities of C 10 H 16 isomers were calculated using a molecular mechanics force field while deducing the favorable reaction pathway from the endo -tetrahydrodicyclopentadiene molecule to the adamantane molecule.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The barrier height energies tabulated in Table 2 for CBS-QB3 (Δ E ‡ CBS-QB3 ) and L-W1X (Δ E ‡ L-W1X ) methods were calculated as the energetic difference between the transition state structure and reactant (for forward reaction) and transition state structure and product (for reverse reaction). Note that the data shown in Tables 1 and 2 serve as an update to computational data calculated using a force field in the work of Engler et al 74 and qualitative experimental data without any computational transition state modeling in the work of Kirchen et al 75 In particular, our high-level data present an improved energy ordering (low to high) compared to the earlier force field work of Engler and co-workers, as follows: 1 , 3 , 12 , 19 , syn - 5 , 18 , 4 , exo - 2 , exo - 8 , 13 , 14 , endo - 2 , anti - 11 , 10 , 7 , endo - 8 , 9 , syn - 11 , anti - 6 , and anti - 5 .…”
Section: Computational Detailsmentioning
confidence: 99%